Polycomb repressive complex 2 controls cardiac cell fate decision via interacting with RNA: Promiscuously or well-ordered - Wang, Gang; Ye, Heng; Wang, Xuchao; Liu, Binbin (Frontiers in Genetics, 2022)
The epigenetic landscape determines cell fate during heart development. Polycomb repressive complex 2 (PRC2) mediates histone methyltransferase activity during cardiac cell differentiation. The PRC2 complex contains the proteins embryonic ectoderm development (EED), suppressor of zeste (SUZ12), the chromatin assembly factor 1 (CAF1) histone-binding proteins RBBP4 and RBBP7, and the histone methyltransferase called enhancer of zeste (EZH2 or EZH1), which incorporates the Su(var)3-9, Enhancer-of-zeste, Trithorax (SET) domain. Cardiac PRC2-deficient mice display lethal congenital heart malformations. The dynamic process of cardiac cell fate decisions is controlled by PRC2 and the PRC2-mediated epigenetic landscape. Although specific individual long noncoding RNAs (lncRNAs) including Braveheart were widely reported to regulate the recruitments of PRC2 to their specific targets, a promiscuous RNA binding profile by PRC2 was also identified to play an essential role in cardiac cell fate decision. In this review, we focus on RNA-mediated PRC2 recruitment machinery in the process of cardiac cell fate decisions. The roles of individual lncRNAs which recruit PRC2, as well as promiscuous RNA binding by PRC2 in heart development are summarized. Since the binding priority of RNAs with different primary and secondary structures differs in its affinity to PRC2, the competitive relationship between individual lncRNAs binding and promiscuous RNA binding by PRC2 may be important for understanding the machinery by which biding of individual lncRNA and promiscuous RNA by PRC2 coordinately control the well-ordered dynamic cardiac cell lineage differentiation process.